A 180 nm technology new 2.5 Gbps burst-mode optical receiver design with automatic gain control and feed-forward created reset - Siek, Liter (2015)
A 180 nm technology new 2.5 Gbps burst-mode optical receiver design with automatic gain control and feed-forward created reset for Ethernet Passive Optical Network (EPON) Systems is presented. To achieve fast response, a reset signal is internally created in the circuit in a feed-forward configuration. In additional, an Automatic Gain Control block is included in the circuit to improve the dynamic range of the optical receiver. Fabricated in a 180 nm CMOS technology, the optical receiver demonstrates a fast response time of less than 10 ns inclusive of the reset creation time. The measured input referred noise is less than 0.97 μArms corresponding to a sensitivity current of 6.79 μArms. A single-ended output reaches a 300 mV swing with input current ranging from 25 μA p–p to 1600 μA p–p . The chip consumes 189 mW from a 1.8 V power supply occupying an area of 1400 μm × 550 μm.